Democratic Multiplicity Perceiving, Enacting, and Integrating Democratic Diversity - Tully, James; Cherry, Keith; Forman, Fonna; Morefield, Jeanne; Nichols, Joshua; Ouziel, Pablo; Owen, David; Schmidtke, Oliver (Social Sciences, 2022)
Our structures of democratic governance are often characterized by 'dysfunctionality', 'hollowing out', and 'gridlock'. This volume proposes an approach grounded in five different modes of democratic praxis. In exploring various democratic traditions, it recognizes that addressing eco-social crises requires coordination and cooperation among them.